The Effect of Warm Water Foot Soaking Therapy on Reducing Blood Pressure in Elderly with Hypertension - Ilham, Rosmin; I. Biahimo, Nur Uyuun; Bima, Siti Cahyani (Universitas Negeri Gorontalo, 2025)
A person's old age will experience a decrease in the function and structure of body organs so that it has an impact on the reduced ability to respond to stimuli that come from inside or outside his body. One of the health problems that tends to occur in the elderly is hypertension. Hypertension is abnormal blood pressure where the systolic pressure is more than 140 mmHg and the diastolic pressure is more than 90 mmHg. The management of hypertension is divided into two, namely pharmacological and non-pharmacological therapy, one of which is foot soaking therapy with warm water to lower blood pressure in the elderly which is easy and effective to be done independently at home. The purpose of this study is to determine the effect of foot soaking therapy with warm water on the reduction of blood pressure in the elderly suffering from hypertension in the working area of the Batudaa Health Center.The design of this study uses a pre-experiment with one group pre and post test given an intervention to the subjects. The population in this study is 116 elderly people who are recorded as hypertension sufferers in the working area of the Batudaa Health Center. The total sample in this study is 16 respondents. The results of the Paired Test of the T-test sample showed a difference in the values in the pre-test and post-test blood pressure data before and after the intervention of foot bath therapy with warm water where a p-value of 0.000 was obtained. It is hoped that the Health Center can provide input on non-pharmacological therapies to the elderly that can prevent, control, and lower blood pressure in addition to consuming anti-hypertensive drugs.